Misconceptions about Acceleration among Prospective Physics Teacher: The Importance of Discussion of Acceleration as a Vector Quantity - Sarkim, Tarsisius (Universitas Sanata Dharma, 2024)
When teaching, researchers found that many students had misconceptions about acceleration. Students' understanding of acceleration is influenced by the terms acceleration and deceleration in everyday life. This misconception results in obstacles to a deeper understanding of motion and an inconsistent understanding of force and its influence on objects. The researcher was curious about what caused this misconception.Researchers suspect that students' misconceptions about acceleration occur because the concept of acceleration is not fully understood as a vector quantity and understanding acceleration is independent of understanding the influence of force on acceleration.This research aims to describe the problem of misconceptions experienced by prospective physics teacher students regarding acceleration and its possible causes.Data was collected over four years, namely from 114 prospective physics teacher students in the first semester of the physics education study program until 2022.They were high school graduates majoring in science where physics, which includes mechanics, is one of the compulsory subjects.Data was collected through multiple choice tests and descriptions. The research results show that the misconceptions experienced by students are: 1) Acceleration is not fully understood as a vector quantity; 2) Students have difficulty explaining the relationship between acceleration and the force that causes it.